2013
DOI: 10.1007/s11999-013-2998-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers to Detect Infection in Revision Hip and Knee Arthroplasties

Abstract: Background A periprosthetic joint infection is one of the most challenging complications associated with THA and TKA. In the diagnostic process for detecting a periprosthetic joint infection, one of the most important steps is analysis of laboratory infection biomarkers. Questions/purposes We investigated the sensitivity and specificity of the biomarkers procalcitonin, interleukin 6 (IL-6), and interferon a (IFN-a) as compared with conventional biomarkers (C-reactive protein [CRP], leukocyte level) for a perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 36 publications
6
65
0
Order By: Relevance
“…Unlike CRP and white blood cell count, procalcitonin values were signifi cantly higher in 45 patients with infection compared with 58 uninfected cases on the day of fever onset, day 1 and day 3. Similar data supporting procalcitonin use in association with other biomarkers such as IL-6 and CRP are reported by Glehr et al ( 2013 ) and by Bottner et al ( 2007 ) in smaller studies investigating febrile patients.…”
Section: Analysis Of the Literature With Critical Discussionsupporting
confidence: 83%
“…Unlike CRP and white blood cell count, procalcitonin values were signifi cantly higher in 45 patients with infection compared with 58 uninfected cases on the day of fever onset, day 1 and day 3. Similar data supporting procalcitonin use in association with other biomarkers such as IL-6 and CRP are reported by Glehr et al ( 2013 ) and by Bottner et al ( 2007 ) in smaller studies investigating febrile patients.…”
Section: Analysis Of the Literature With Critical Discussionsupporting
confidence: 83%
“…Procalcitonin has also been used as a marker of systemic infection, but its role in the diagnosis of a local infection such as PJI is limited because the threshold of procalcitonin in patients with local infection overlaps significantly with its normal range (low specificity) [13, 14, 21]. Nevertheless, recent studies did not confirm that IL-6 and procalcitonin outperform conventional blood biomarkers for diagnosis of PJI [22]. …”
Section: Serum Biomarkersmentioning
confidence: 99%
“…One study included 124 revision arthroplasty procedures and found that procalcitonin, interleukin 6, and interferon α were not superior to CRP [40]. The other study utilized enzyme-linked immunosorbent assay (ELISA) to measure the levels of antimicrobial peptides such as human β-defensin 2, human β-defensin 3, and cathelicidin LL-37 as well as inflammatory cytokines such as interleukin (IL)-1β, IL-4, IL-6, IL-17A, interferon-γ, and tumor necrosis factor (TNF)-α in 15 patients with PJI and 20 patients with aseptic revision [28].…”
Section: Diagnosismentioning
confidence: 99%